2018
DOI: 10.3892/etm.2018.6004
|View full text |Cite
|
Sign up to set email alerts
|

Rapamycin provides anti‑epileptogenic effect in a rat model of post‑traumatic epilepsy via deactivation of mTOR signaling pathway

Abstract: The mammalian target of rapamycin (mTOR) signaling pathway has attracted much attention in recent years. However, the contribution of mTOR activation to the development of post-traumatic epilepsy (PTE) remains largely unknown. The purpose of the present study was to investigate the activation of mTOR signaling in a rat model of FeCl2-induced PTE, and to explore the potential effect of its specific inhibitor rapamycin. The results indicated that the expression levels of p-mTOR and p-P70S6K, the overactivation b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 32 publications
0
8
0
1
Order By: Relevance
“…Rapamycin inhibits mTORC1 and has been shown to have antiseizure effects . Treatment with rapamycin during or after the initial epileptogenic injury has shown to reduce the percentage of mice that developed post‐traumatic epilepsy and the frequency of spontaneous seizures, as well as neuronal degeneration . Similar results have also been shown in the post‐SE and neonatal hypoxia models of acquired epilepsy .…”
Section: Mechanistic Target Of Mammalian Rapamycin Pathwaymentioning
confidence: 54%
“…Rapamycin inhibits mTORC1 and has been shown to have antiseizure effects . Treatment with rapamycin during or after the initial epileptogenic injury has shown to reduce the percentage of mice that developed post‐traumatic epilepsy and the frequency of spontaneous seizures, as well as neuronal degeneration . Similar results have also been shown in the post‐SE and neonatal hypoxia models of acquired epilepsy .…”
Section: Mechanistic Target Of Mammalian Rapamycin Pathwaymentioning
confidence: 54%
“…In addition to inflammatory changes, there are a variety of other molecular alterations after TBI that have been implicated in the development of PTE. The mTOR signaling pathway, a regulator of cell metabolism, proliferation, and differentiation, has also been implicated in both TBI recovery 34 and seizures 35 . Surgically resected tissue samples from patients with temporal lobe epilepsy show increased expression of phosphorylated proteins mTOR, s6, and Akt, consistent with mTOR overactivity 36 .…”
Section: Discussionmentioning
confidence: 99%
“…mTOR inhibition supports a causative role of this pathway in altered seizure susceptibility 37 . In rodent studies of PTE, the mTOR inhibitor, rapamycin, has demonstrated antiepileptogenic effects 34 . Although mTOR signaling alterations have been shown in various zebrafish models of seizures, 38–40 they have not been investigated in zebrafish TBI or PTE.…”
Section: Discussionmentioning
confidence: 99%
“…In a rat model of FeCl 2 -induced post-traumatic epilepsy (PTE), p-mTOR and p-P70S6K are increased significantly in the hippocampus and perilesional cortex [138]. Rapamycin administration decreases mTOR activity markers while reducing the frequency and number of behavioral seizures and epileptic brain injury [138].…”
Section: Ischemic/hemorragic Stroke and Brain Traumamentioning
confidence: 99%